IoT-Based Energy Consumption Analysis of Electric Vehicles: The Effect of VESC Motor Current Limits - Fahri Ardianto; Ulinuha, Agus (PTE FTK UIN Ar-Raniry, 2026)
This study presents an IoT-based battery monitoring system and analyzes the effect of the VESC motor current limit on battery current and energy consumption. The research focuses on an electric vehicle prototype developed by the Electric Car Research Center (ECRC) at the Faculty of Engineering, Universitas Muhammadiyah Surakarta. The system integrates an ESP32-S3, PZEM-017 sensor, Neo-7M GPS, and Firebase database for real-time monitoring. Experiments were conducted at five current limits 10-30 A with three replications. Results show that increasing the current limit from 10 A to 30 A increased average battery current from 1.30 A to 3.53 A (F(4,10) = 285.47, p < 0.001, R² = 0.991), energy consumption from 6.54 Wh to 12.90 Wh (F(4,10) = 298.66, p < 0.001, R² = 0.992), and torque from 3.60 Nm to 5.43 Nm (F(4,10) = 142.35, p < 0.001, R² = 0.983), but decreased energy efficiency from 152.90 to 77.52 km/kWh. The expanded uncertainties for all measurements remained below 1.5%, confirming high data precision. These findings quantify the performance-efficiency trade-off, providing a basis for optimizing current limit settings in energy-efficient electric vehicles.